Public Utilities’ Corporate Growth and Environmental Conservation: Evidence from Japan - Tsujimoto, Masao (International Journal of Energy Economics and Policy, 2023)
This study explores how public utilities in Japan demonstrate the achievement of both growth and environmental conservation, by using financial performance and environmental impact data from publicly traded companies of power, gas, transport, telecommunication, and postal services before and during the COVID-19 pandemic. First, the regression analyses confirm the Environmental Kuznets Curve (EKC) hypothesis and an inverted N-shaped curve in 2019, 2020, and 2021. Second, the deciding factors are the result of the interaction of the following five points, which have been more encouraged and promoted in Japan in recent years: (1) regulatory reforms such as energy market opening; (2) investors’ emphasis on environment, society, and governance (ESG); (3) guidelines and assessments by economic organizations, rating agencies, and environmental nonprofit groups; (4) citizens’ professional ethics and willingness for environmental conservation and social contribution; and (5) endogenous efforts by the public utilities as members of society. Third, an approach that focuses on ESG and total shareholders return (TSR) can contribute not only to the achievement of both growth and environmental conservation but also to the expansion of the academic literature.